Addressing the oxamniquine in vitro-in vivo paradox to facilitate a new generation of anti-schistosome treatments - Katalin Toth; Sevan Alwan; Susan Khan; Stanton F. McHardy; Philip T. LoVerde; Michael D. Cameron (International Journal for Parasitology: Drugs and Drug Resistance, 2023)
The antischistosomal drug oxamniquine, OXA, requires activation by a sulfotransferase within the parasitic worm to enable killing. Examination of the pharmacokinetic/pharmacodynamic (PK/PD) relationship for OXA identified an in vitro-in vivo paradox with the maximal clinical plasma concentrations five-to ten-times lower than the efficacious concentration for in vitro schistosomal killing. The parasite resides in the vasculature between the intestine and the liver, and modeling the PK data to determine portal concentrations fits with in vitro studies and explains the required human dose. In silico models were used to predict murine dosing to recapitulate human conditions for OXA portal concentration and time course. Follow-up PK studies verified in mice that a 50–100 mg/kg oral gavage dose of OXA formulated in acetate buffer recapitulates the 20–40 mg/kg dose common in patients. OXA was rapidly cleared through a combination of metabolism and excretion into bile. OXA absorbance and tissue distribution were similar in wild-type and P-gp efflux transporter knockout mice. The incorporation of in vitro efficacy data and portal concentration was demonstrated for an improved OXA-inspired analog that has been shown to kill S. mansoni, S. haematobium, and S. japonicum, whereas OXA is only effective against S. mansoni. Second-generation OXA analogs should optimize both in vitro killing and physiochemical properties to achieve high portal concentration via rapid oral absorption, facilitated by favorable solubility, permeability, and minimal intestinal metabolism.